ANALISIS RASIO PROFITABILITAS PADA PT. SUMBER ALFARIA TRIJAYA, TBK (ALFAMART) - Nusale, Grimaldy E. J; Mangindaan, J. V; Mukuan, Danny D. S (Sam Ratulangi University, 2017)
To assess whether or not the company's healthy performance lies in its financialperformance. To know the level of achievement or success of the company, then thenecessary financial indicators. These financial indicators can be obtained from financialstatements. The financial statements used are balance sheet and income statement. Tofind out how far the development of the company from year to year required ananalysis. The most important aspect in analyzing financial statements is profitability, asa measure of management effectiveness indicated by the profit generated from the saleof corporate investment. An analysis tool that can be used to measure the success rate ofa company in generating profit is to use profitability ratio analysis. The purpose of thisstudy is to determine the financial performance of PT. Sumber Alfaria Trijaya, Tbkreviewed from profitability ratios. Sunyoto (2013) profitability ratio is the ability toprofit from its business. Financial performance analysis tool based on profitabilityratios used in this study is RETURN ON ASSET, RETURN ON EQUITY, MARGINPROFIT NET AND GROSS PROSIT MARGIN from 2012 – 2015. Based on the resultsof the analysis it has been seen that the average RETURN ON ASSET is 5%, below theindustry standard average of 20% and return on equity has a downward trend wherethe average RETURN ON EQUITY is 16 , 60% is still below the industry standardaverage of 30% and net profit margin is 18.15% is still below industry standard and theresult of Gross Profit Margin always increases , The average GROSS PROSITMARGIN showed poor results because only 1.48% was still below the industry averageof 20%. This research is expected to enrich the concept of knowledge about Profitabilityratio analysis. The results of this study are expected to provide meaningful informationto the management of the company regarding the position of Profitability of thecompany.Key Word : Ratio Profitability